Evaluation of the relationship between serum cholesterol levels and multiple sclerosis disease activity - Seferoglu, Meral; Koca, Nizameddin (The European Research Journal, 2020)
Objectives: Multiple sclerosis (MS) is an immune-mediated, inflammatory, demyelinating, neurodegenerative disease of the central nervous system affecting young adults. Cholesterol and lipids are essential components of nerve cells and are abundant in the myelin sheath. In this study, we aimed to investigate the relationship between plasma cholesterol levels and severity of the disease and lesion burden in cranial magnetic resonance imaging. Methods: A total of 70 patients (22 males and 48 females) with the diagnosis of MS were included in the study. Age, gender, duration of disease, Expanded Disability Status Scale (EDSS) scores, total number of relapses since diagnosis, current treatment and lipid levels of all participants were recorded. The patients were grouped according to EDSS scores, total number of relapses and number of lesions observed in cranial MRI and the data were compared among the groups. Results: The mean age was 38.62 ± 9.94 years and the duration of the disease was 7.50 ± 5.88 years. The mean EDSS score was 2.80 ± 1.69. Total cholesterol, triglyceride and LDL levels were found to be significantly higher in the group with more than 3 relapses. Patients with > 9 lesions were older and EDSS scores were higher. In correlation analysis; there was a significant positive correlation between total cholesterol and LDL levels and EDSS scores and disease duration. Conclusions: We found that the number of relapses, disease duration, and EDSS scores were significantly correlated with cholesterol levels. The changes in plasma cholesterol levels which are easily accessible laboratory tests may provide insight into MS disease activity and progression.